Valutare è ricerca educativa - Achille Maria Notti; Rosa Vegliante (LED Edizioni Universitarie, 2014)
Evaluation: a Kind of Educational Research Educational assessment, meant as the mere act or effect of the interpretation of student learning outcomes, has greatly changed. The traditional task of assessment is supported by a series of operations setting and interpreting educational acts which affects not only the results, but also the processes and the context in which the actors involved operate in the educational institution at different levels (micro-meso and macro). This kind of evaluation can be considered educational research aimed at gaining a knowledge and understanding of educational events in order to identify problematic nodes with a view to taking action to change and to improve outcomes. Consequently, better results are directly proportional to quality improvement processes. A quality process is characterized and supported by multiple educational/evaluative interventions, which can rationalize decision-making, determine the tasks to be performed, make a change through a planned and contextualized project. Educational outcome measurement is meaningful only if considered from a systemic point of view so as to develop educational research and experiment new teaching strategies.